Dangers of Gendering: The Case of Pre-Raphaelitism - Jukić, Tatjana (Array, 2008)
The text analyzes what in Pre-Raphaelitism has been identified as androgyny, as the tropology that figures away the underanalyzed residue of sexuality and of conception, both in Pre-Raphaelitism and in its critique.